The A-B-A’ structure as a social ‘return’ in opera buffa - Filocamo, Gioia (Schweizer Jahrbuch für Musikwissenschaft, 2026)
The structure A-B-A', typical of a tripartite aria of an eighteenth-century opera seria, could also describe the dramaturgy implied in the plots of the three opere buffe by Da Ponte - Mozart. This structure restores the emotional stability of the characters: at the beginning, they seem to live in a stable world (A), then the characters experience different emotions (B), and at the end of the story, they return to their initial situation. The action’s spiral shows a social circle that finally re-establishes its original order regained after some lively diversions. Every plot displays a vibrant mixed society that appears, at the same time, very static: in fact, the aristocrats confirm themselves as the ruling class that will not lose any privileges by mixing with the medium or low class. The circular narrative of the three stories will overtake time and experiences that run in their B parts, regaining a new A' stability that seems the ‘correct’ one recalling every starting point of the three operas.